How can community grants promote gender-inclusive development in fragile settings? Insights from rural Nigeria - Kyle, Jordan; Adeyanju, Dolapo; Adida, Claire; Arriola, Leonardo; Carrillo, Lucia; Fisher, Rachel; Iraoya, Augustine Okhale; Kosec, Katrina; Matanock, Aila; Mo, Cecilia H. (International Food Policy Research Institute, 2025)
Community-driven development (CDD) programs aim to shift decision-making to the local level by empowering communities to prioritize, design, and implement projects that address their most pressing needs. These programs have gained global traction as vehicles for service delivery and empowerment, especially in fragile contexts with weak state capacity. These programs leverage communities’ understanding of local needs and their unique ability to deploy resources in conflict-affected, unstable, or highly remote areas that are operationally hard to reach for traditional development programs. However, evidence remains limited on how to structure CDD programs to ensure inclusive participation from a wide range of community members, particularly women, who tend to participate in community and public affairs at lower levels than men in these settings (Takeshima et al., 2024).